Confirmatory factor analysis of the Spanish version of the Gamblers’ Beliefs Questionnaire in a sample of Argentinean gamblers - Pilatti, Angelina (2016)
Cognitive distortions are related to gambling frequency and gambling severity.Having a culturally sensitive measure to assess cognitive distortions will facilitate the early detection of people who might be at risk of developing problematic gambling behaviors. The Gamblers´ Beliefs Questionnaire was translated into Spanish (GBQ-S) but no previous study explored the structure of the GBQ-S in a non-US sample with different levels of gamblinginvolvement. The present study examined the factor structure of the GBQ-S in a community sample of gamblers from Argentina. It also analyzed the association between cognitive distortions and type of gambling activity and frequency of gambling behaviors and the predictive utility of theGBQ-S on gambling severity. Participants: 508 youth and adults completed the GBQ-S. Results: The CFA showed an overall acceptable fit to the data confirming the proposed two-factor model. Scores of the two GBQ sub-scales were positively and significantly correlated with scores on gambling severity. Cognitive distortions have a significant effect on gambling severity aftercontrolling for frequency of engagement in gambling activities. Luck and perseverance, but not illusion of control, was positively related to gambling severity. Discussion: scores measured by the GBQ-S exhibit adequate psychometric properties for the accurate assessment of cognitive distortions across adults and youth from the general community of Argentina.